Asset recombination in international partnerships as a source of improved innovation capabilities in China. Issue 4 (17th November 2014) - Collinson, Simon C.; Narula, Rajneesh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to examine how multinational enterprises (MNEs) and local partners, including suppliers, customers and competitors in China, improve their innovation capabilities through collaboration. This collaboration was analysed as a three-way interaction between the ownership-specific (O) advantages or firm-specific assets (FSAs) of the MNE subsidiary, the FSAs of the local partner and the location-specific assets of the host location. Design/methodology/approach – The propositions are examined through a survey of 320 firms, supplemented with 30 in-depth case studies, based in Mainland China. Findings – It is found that the recombination of asset-type (Oa) FSAs and transaction-type (Ot) FSAs from both partners leads to new innovation-related ownership advantages, or "recombinant advantages". Ot FSAs, in the form of access to local suppliers, customers or government networks are particularly important for reducing the liability of foreignness for MNEs. Originality/value – The study reveals important patterns of reciprocal transfer, sharing and integration for different asset categories (tacit, codified) and different forms of FSA and explicitly links these to different innovation performance outcomes. The paper reports on these findings, making an empirical contribution in an important context (China-based partnerships). This paper also contributes to conceptual developments, connecting various kinds of FSA, tacit and codifiable assets and "recombinant advantages". Limited conceptual, methodological and empirical contributions are made in linking asset integration with (measurable) innovation performance outcomes in international partnerships.